Scale for time and space experience in anxiety (STEA): phenomenology and its clinical relevance - Lu, Cheng-Ju; Goheen, Josh; Wolman, Angelika; Lucherini Angeletti, Lorenzo; Arantes-Gonçalves, Filipe; Hirjak, Dusan; Wolff, Annemarie; Northoff, Georg (Journal of affective disorders, 2024)
Anxiety is a pervasive emotional state where, phenomenologically, subjects often report changes in their experience of time and space. However, a systematic and quantified examination of time and space experience in terms of a self-report scale is still missing which eventually could also be used for clinical differential diagnosis. Based on historical phenomenological literature and patients' subjective reports, we here introduce, in a first step, the Scale for Time and Space Experience of Anxiety (STEA) in a smaller sample of 19 subjects with anxiety disorders and, in a second step, validate its shorter clinical version (cSTEA) in a larger sample of 48 anxiety subjects. The main findings are (i) high convergent and divergent validity of STEA with both Beck Anxiety Inventory (BAI) (r = 0.7325; p < 0.001) and Beck Depression Inventory (BDI) (r = 0.7749; p < 0.0001), as well as with spontaneous mind wandering (MWS) (r = 0.7343; p < 0.001) and deliberate mind wandering (MWD) (r = 0.1152; p > 0.05), (ii) statistical feature selection shows 8 key items for future clinical usage (cSTEA) focusing on the experience of temporal and spatial constriction, (iii) the effects of time and space experience (i.e., for both STEA and cSTEA scores) on the level of anxiety (BAI) are mediated by the degree of spontaneous mind wandering (MWS), (iv) cSTEA allows for differentiating high levels of anxiety from the severity of comorbid depressive symptoms, and (v) significant reduction in the cSTEA scores after a therapeutic intervention (breathing therapy). Together, our study introduces a novel fully quantified and highly valid self-report instrument, the STEA, for measuring time-space experiences in anxiety. Further we develop a shorter clinical version (cSTEA) which allows assessing time space experience in a valid, quick, and simple way for diagnosis, differential diagnosis, and therapeutic monitoring of anxiety.